Administration of metformin cream prevented the increase of melanin amount in ultraviolet B exposed guinea pigs (Cavia porcellus) skin - Vitia Tandy; Wimpie Pangkahila; A.A.G.P. Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Ultraviolet exposure has been known to be the most significant factor influencing skin pigmentation, includes in increasing melanin amount. It is caused by the effect of ultraviolet B radiation in increasing melanin synthesis. Topical administration of metformin can inhibit the melanogenesis process by decreasing the level of cAMP and inhibiting PKC-β activation. This research aimed to prove that administration of 0.5% metformin cream prevented the increase of melanin amount in ultraviolet B exposed guinea pigs (Cavia porcellus) skin. Methods: This study was a true experimental research using posttest only control group design. Thirty six male guinea pigs were divided into control and treatment group. Base cream was administered to the control group and 0.5% metformin cream was administered to the treatment group once daily. All of the guinea pigs were exposed to ultraviolet B radiation at 390 mJ/cm2 three times a week. Punch biopsy was conducted two weeks after treatment to obtain skin samples for histologic preparations. Thereafter, those samples were stained with Masson-Fontana to examine the melanin amount. Finally, the average melanin amount in both groups was compared. Results: All samples in both groups successfully made to the end of the research without drop out. This research found that the average amount of melanin in treatment group, which was 2.04 ± 0.62%, was significantly lower than control group, which was 18.57 ± 1.68% (p < 0.001). Conclusion: Administration of 0.5% metformin cream prevented the increase of melanin amount in ultraviolet B exposed guinea pigs (Cavia porcellus) skin.